CODE SWITCHING AND CODE MIXING IN NOVEL RAHASIA MEEDE BY E. S. ITO: ALIH KODE DAN CAMPUR KODE PADA NOVEL RAHASIA MEEDE KARYA E. S. ITO - Aditya Rachman; Vivi Indriyani; Ayu Gustia Ningsih (LLDIKTI Wilayah X, 2023)
A novel is a literary genre that depict linguistic phenomena in real life. It serves not only as a source of enjoyable entertainment, but also as a mirror of the language reality that exists in society. The purpose of this research is to describe the forms of code switching and code mixing in the novel Rahasia Meede by E.S. Ito. This research is a descriptive qualitative study. The source of data in this research is the novel Rahasia Meede by E.S. Ito. The object of this research is the actual use of code switching and code mixing in the novel. The results of this research show that the characters in the novel use or mix Dutch, English, Spanish, Hindi, Latin, Mentawai, Nias, and Indonesian languages in different situations. The forms of code switching in this research are switches from Indonesian to Dutch, English, Indian, Mentawai, Nias, Bataknese, and Latin languages. The types of code mixing found are mixes of Dutch, English, Aceh, Spanish, Mentawai, Latin, Minangkabau, and Hindi languages.